Indigenous Land Boundary Dispute between Awi Clan and Afar Clan in the Abepura District, Jayapura City - Palenewen, James Yoseph; Solossa, Marthinus (Journal of Progressive Law and Legal Studies, 2023)
Land border disputes often arise both in rural and urban areas with various problems related to customary land boundaries which can trigger clashes or conflicts between groups. Knowing the things that cause disputes in customary land boundary rights between the Awi and Afar clans and to find out the obstacles and obstacles faced in resolving customary land border disputes between the two groups. The approach used in research is empirical method, namely through field research or direct observation at research locations in order to obtain clarity about the object under study. The results of this research show that the dispute between the Awi clan (in Nafri village) and the Afar clan (in Enggros-Tobati village) occurred because the Afar clan put up a land claim flag on one of the red bridge road axles, but the Awi clan disagreed because they thought the land belonged to their group. Barriers and obstacles in resolving customary land border disputes between the Awi and Afar clans are only two factors, namely internal and external.